Unilateral winged scapula: Clinical and electrodiagnostic experience with 128 cases, with special attention to long thoracic nerve palsy. Issue 6 (24th February 2018) - Seror, Paul; Lenglet, Timothee; Nguyen, Christelle; Ouaknine, MichaëL; Lefevre‐Colau, Marie Martine
ABSTRACT: Introduction : In this study we report a large series of patients with unilateral winged scapula (WS), with special attention to long thoracic nerve (LTN) palsy. Methods : Clinical and electrodiagnostic data were collected from 128 patients over a 25‐year period. Results : Causes of unilateral WS were LTN palsy ( n  = 70), spinal accessory nerve (SAN) palsy ( n  = 39), both LTN and SAN palsy ( n  = 5), facioscapulohumeral dystrophy (FSH) ( n  = 5), orthopedic causes ( n  = 11), voluntary WS ( n  = 6), and no definite cause ( n  = 2). LTN palsy was related to neuralgic amyotrophy (NA) in 61 patients and involved the right side in 62 patients. Discussion : Clinical data allow for identifying 2 main clinical patterns for LTN and SAN palsy. Electrodiagnostic examination should consider bilateral nerve conduction studies of the LTN and SAN, and needle electromyography of their target muscles. LTN palsy is the most frequent cause of unilateral WS and is usually related to NA. Voluntary WS and FSH must be considered in young patients. Muscle Nerve 57 : 913–920, 2018